2008
DOI: 10.1002/ptr.2459
|View full text |Cite
|
Sign up to set email alerts
|

An Iranian herbal‐marine medicine, MS14, ameliorates experimental allergic encephalomyelitis

Abstract: Multiple sclerosis is an inflammatory and demyelinating disease of the central nervous system which mainly affects young adults. To overcome wide spectrum troublesome symptoms of multiple sclerosis which affects the quality of life both in patients and their families, new drugs and remedies have been examined and offered. The preclinical beneficial effects of different medicines have mostly been examined in an animal model of multiple sclerosis called experimental allergic encephalomyelitis (EAE). In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Identification of new anti-inflammatory agents to enhance axon myelination would present new therapeutic approaches to inhibit and possibly reverse the disease progression (27, 28). Our findings indicated that herbal drugs diminished the neurological signs of EAE, which was supported by prior studies (19, 29). MS14 as an anti-inflammatory remedy decreased T-cell proliferation and proinflammatory cytokines levels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Identification of new anti-inflammatory agents to enhance axon myelination would present new therapeutic approaches to inhibit and possibly reverse the disease progression (27, 28). Our findings indicated that herbal drugs diminished the neurological signs of EAE, which was supported by prior studies (19, 29). MS14 as an anti-inflammatory remedy decreased T-cell proliferation and proinflammatory cytokines levels.…”
Section: Discussionsupporting
confidence: 91%
“…All animals were housed separately in each cage and MS14 was administrated to the treatment group orally. They were also fed with MS14-containing (30 %) diet from the day of immunization (19) to the end of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals in treated group received food containing MS14 (30% of food weight) from the day of immunization to the end of the study. MS14 powder was a gift from Pharmacology Department of Shahed University by decedent Dr. Amrollah Ahmadi [12]. …”
Section: Methodsmentioning
confidence: 99%
“…It has anti-inflammatory and immunomodulatory effects through reduction of TNF-α and IL-1β production in MS and EAE [10]. Due to these anti-inflamatory effects it is considered as a potential therapy for MS [11, 12]. However, effects of MS14 on oxidative stress and the mechanisms underlying regulates the immune system remain unknown.…”
Section: Introductionmentioning
confidence: 99%